Exploring ionic liquid assisted pretreatment of lignocellulosic biomass for fabrication of green composite - Moniruzzaman, M. (Japan Institute of Energy, 2017)
Ionic liquids (ILs) pretreatment has emerged as the promising technology toward environmentally benign conversion of lignocellulosic residues into high value cellulosic fiber as sustainable raw material for biocomposite manufacturing. In this work, the impact of an ionic liquid (IL) 1-ethyl-3-methylimidazolium diethylphosphate (emim dep) pretreatment of oil palm frond (OPF) on the flexural properties of the composite board has been reported. Ionic liquid pretreatment of OPF fiber under high solids loading (IL/biomass ratio = 1.0) was conducted prior to compounding with thermoplastic starch which was used as binder polymer. Effect of IL pretreatment on OPF fiber was assessed by employing Fourier Transform Infrared Spectroscopy technique. IL treated composite board was found to exhibit superior flexural properties than that of untreated board. Flexural strength was increased from 10 MPa for untreated composite to 12.75 MPa for composites fabricated from IL treated OPF particles. The obtained results evidenced that the IL pretreatment could be a promising, cost-efficient and benign approach for conversion of agricultural waste into high value engineered composite panels. The study plainly demonstrates that IL based pretreatment could be a green technology for effective utilization of lignocellulosic waste biomass in the biocomposite manufacturing.